2016
DOI: 10.1007/s00360-016-0985-1
|View full text |Cite
|
Sign up to set email alerts
|

The proximal gastric corpus is the most responsive site of motilin-induced contractions in the stomach of the Asian house shrew

Abstract: The migrating motor complex (MMC) is responsible for emptying the stomach during the interdigestive period, in preparation for the next meal. It is known that gastric phase III of MMC starts from the proximal stomach and propagates the contraction downwards. We hypothesized that a certain region of the stomach must be more responsive to motilin than others, and that motilin-induced strong gastric contractions propagate from that site. Stomachs of the Suncus or Asian house shrew, a small insectivorous mammal, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…Similar results have been reported in shrew and human stomachs [29,30], suggesting that the motilin-induced contractile response is anatomically region-specific.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results have been reported in shrew and human stomachs [29,30], suggesting that the motilin-induced contractile response is anatomically region-specific.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, Dudani et al . [30] reported that the contractile response to motilin in house shrew was more prominent in the gastric fundus than in the antrum. In general, the contractile response in mice to various stimulation such as acetylcholine, serotonin, and electrical field stimulation was more prominent in the gastric fundus than in the antrum [31].…”
Section: Discussionmentioning
confidence: 99%
“…Motilin, SP, SS, and VIP are closely associated with gastric functions. MOT and SP will be increased in GU development ( Dudani et al, 2016 ). In conversely, SS ( Coskun et al, 2013 ) and VIP ( Kasacka et al, 2015 ) have protective functions for stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Motilin (MOT) modulates gastric contraction via cholinergic, adrenergic, serotonergic, and NO neurons ( Mondal et al, 2011 ), and is associated with emptying the stomach during the interdigestive period ( Dudani et al, 2016 ). Substance P (SP) belongs to an undecapeptide member of the tachykinin neuropeptide family.…”
Section: Methodsmentioning
confidence: 99%